Bisnis Produk Halal antara Peluang dan Tantangan, Problematika dan Solusinya - Warto Warto; Zainal Arif (Al-Ulum, 2020)
This study aims to examine the halal business opportunities, challenges and solutions in Indonesia. This research uses descriptive qualitative method by using documentation data in the form of books, reports from official institutions such as BPS, OJK, BI, Ministry of Trade, Kemenpan and scientific journals. The results of a study of several literatures found that Indonesia actually has a huge opportunity to become the center of the world's halal business. This can be seen from several indicators between the high level of the Muslim population and the high level of consumption. However, the attitude of business actors who tend to be unaware, pursue more profits, lack of government attention, protect business players more than consumers, the low public response to halal products is a major obstacle. The main solution is to accelerate the application of the JPH Law as a legal umbrella, awareness of entrepreneurs and business people, by making halal certification a part of excellent service, and community support.